Implementasi Manajemen Arsip dalam Peningkatan Kualitas Pelayanan Tata Usaha - Umi Kalsum; Ramdanil Mubarok; Ismail Rahmat (BEduManagers Journal : Borneo Educational Management and Research Journal, 2026)
This study aims to analyze the implementation of records management, its impact on improving the quality of administrative services, and the problems and solutions of archive management at SMK Islam Nurul Hikmah Sangatta. This study employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving the principal and administrative staff and were analyzed using the Miles and Huberman model, including data condensation, data display, and conclusion drawing, with data validity tested through source and technique triangulation. The findings indicate that records management has been implemented through systematic recording, classification, and storage of archives, although it is still managed manually and has not been supported by digitalization. The implementation has positively contributed to the improvement of administrative service quality, particularly in terms of speed, efficiency, and accessibility of information. However, several obstacles remain, including limited facilities, the absence of digital systems and data backup, and the lack of written guidelines. Therefore, strengthening a standardized digital-based records management system is necessary to improve the quality of administrative services effectively and sustainably.